2020
DOI: 10.1080/02640414.2020.1717286
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional comparison of body composition and resting metabolic rate in Premier League academy soccer players: Implications for growth and maturation

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 23 publications
6
28
0
Order By: Relevance
“…These results are in agreement with the data of a previous study on Indian soccer players, where an increase in REE of about 400 kcal/day from the ages of 10 to 13 was also noticed [31]. A similar effect was observed by Hannon et al, who also showed an increase in REE between the U12 and U14 (Football Academy Categories) age groups [32].…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with the data of a previous study on Indian soccer players, where an increase in REE of about 400 kcal/day from the ages of 10 to 13 was also noticed [31]. A similar effect was observed by Hannon et al, who also showed an increase in REE between the U12 and U14 (Football Academy Categories) age groups [32].…”
Section: Discussionsupporting
confidence: 93%
“…In the U16 and U18 age-groups (one-match per weekly microcycle), HSR distance was similar to that of adult EPL players during a two and a three match week, though sprint distance was significantly less than adult players for a two (~520 m) and three (~1000 m) match week (Anderson et al, 2016). In addition to the physical developments described above, it is noteworthy that academy players possess considerably less FFM than adult players (Hannon et al, 2020), an important component that is closely associated with power and speed production (Murtagh et al, 2018;Wrigley et al, 2014). When considered in this way, our data demonstrate that whilst academy players in the U16 and U18 age-groups are capable of achieving the training and match volumes experienced by adult EPL players, they do not achieve the absolute intensities completed by elite adult soccer players.…”
Section: Discussionmentioning
confidence: 71%
“…stature, body mass and fat free mass), we also observed an increase in RMR of approximately 400 kcalday -1 between ages 12 and 16 (i.e. the period corresponding with peak height velocity, PHV), thus highlighting the requirement to adjust total energy intake accordingly (6). However, given that RMR only represents a proportion of total daily energy expenditure (TEE) (7), there is…”
Section: Introductionmentioning
confidence: 83%
“…In this regard, we recently quantified changes in body composition and resting metabolic rate (RMR) in a cohort of male English Premier League academy soccer players from U12 -U23 age-groups (6). In accordance with progressive increases in physical characteristics (e.g.…”
Section: Introductionmentioning
confidence: 99%